A CHECKLIST OF HOUSE FLIES (DIPTERA: MUSCIDAE) FROM NORTHEAST INDIA - MITRA, B.; AHMED, SEEMIN; SHARMA, R.M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
A total of 108 species of 28 genera belonging to 6 subfamilies of houseflies so far known are enumerated in this checklist from Northeast India, comprising seven states viz. Arunachal Pradesh, Assam, Manipur, Meghalaya. Mizoram. Nagaland and Tripura.